Attention Deficit-Hyperactivity Disorder Group Visits Improve Parental Emotional Health and Perceptions of Child Behavior. Issue 6 (July 2018) - Bauer, Nerissa S.; Sullivan, Paula D.; Szczepaniak, Dorota; Stelzner, Sarah M.; Pottenger, Amy; Ofner, Susan; Downs, Stephen M.; Carroll, Aaron E.
ABSTRACT: Objective: Group visits (GVs) are a promising intervention, but more work is needed to establish intervention effects. The objective was to evaluate the effectiveness of GVs and compare them with individual visits (INDs) for chronic care of attention deficit-hyperactivity disorder (ADHD). Methods: Caregivers and children (6–12 yrs) with ADHD participated in a comparative effectiveness trial from April 2014 to June 2015. Families were offered ADHD follow-up every 3 months as GVs versus INDs. Outcomes included ADHD core symptoms, child functioning at home, quality of life, perceived social support, and ADHD-related parenting challenges. Change scores from baseline to the study end were examined for parent and child outcomes within and between treatment conditions. Results: Ninety-one children from 84 families participated. Eighteen families withdrew or were lost to follow-up. GV families attended more visits over 12 months, had significant improvement in mean parental emotional health ( p = 0.04), and had a greater decrease in challenges related to misbehavior compared with IND families ( p < 0.03). GV families experienced significant improvements in child functioning at home ( p = 0.01) and reported more time for themselves, other siblings, and routine household activities ( p < 0.01). Children receiving care as INDs reported a significant drop in mean emotional health. There were no significant changes in other outcomes. Conclusion: Families participating in GVs experienced multiple improvements related to family functioning and attended more follow-up visits. Findings confirm the effectiveness of the GV intervention in delivering critical parenting support as part of ADHD management.